Analysis of purchasing habits and investment decision-making among consumers in southern Sonora. - Leyva Herrera, Ivonne Jovana; Murillo Félix, Cecilia Aurora; Galaviz Zamora, Marisol (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To identify the existence of statistically significant differences in planned and impulsive purchasing habits between individuals who have made financial investments and those who have not.MATERIAL AND METHOD: A quantitative, descriptive, and correlational approach was applied with a non-probabilistic sample of 513 consumers from Navojoa, Sonora. Validated scales were used to measure purchasing habits, showing high reliability (Cronbach’s Alpha = .873). Data were analyzed using descriptive statistics and the Student’s t-test.RESULTS: The findings show no significant difference in planned purchasing habits between the groups (p > 0.05). However, a significant difference was identified in impulsive purchasing habits (p = 0.005), which were more frequent among those who have not made investments.CONCLUSIONS: Impulsive purchasing habits negatively affect individuals’ willingness to invest, whereas planned purchasing habits do not have a direct impact. This research highlights the urgency of promoting financial education and responsible consumption habits as a strategy to improve investment decision-making and individual financial well-being, contributing originality by exploring this relationship in the Mexican context.
Keywords: purchase; investment; impulsive.